2011
DOI: 10.1590/s0103-64402011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Non-nutritive sucking habits, anterior open bite and associated factors in Brazilian children aged 30-59 months

Abstract: The aim of the present study was to investigate the prevalence of non-nutritive sucking habits and anterior open bite as well as their main causes (associated factors) in Brazilian children aged 30-59 months. A cross-sectional study was carried out during the National Immunization Day for polio in the city of Recife in the northeastern region of Brazil. The sample was made up of 1,308 children. Data were collected from interviews with mothers or guardians as well as from clinical examinations carried out by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
4
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 8 publications
8
51
4
22
Order By: Relevance
“…Another Brazilian study reports a 69.9% prevalence rate of malocclusion in the anterior region, using a cutoff point of > 2 mm for determining increased overjet. 1 Since young children may exhibit nonnutritive sucking habits, 24 it is important to stress than the mean age of the children in the present study was 4.25 (SD = 0.83) years, whereas mean age in the study by Kramer et al 1 was 3.5 (SD = 1.0) years. This result may show that the damage caused by nonnutritive sucking habits can be corrected spontaneously after cessation of these habits.…”
Section: Discussioncontrasting
confidence: 53%
“…Another Brazilian study reports a 69.9% prevalence rate of malocclusion in the anterior region, using a cutoff point of > 2 mm for determining increased overjet. 1 Since young children may exhibit nonnutritive sucking habits, 24 it is important to stress than the mean age of the children in the present study was 4.25 (SD = 0.83) years, whereas mean age in the study by Kramer et al 1 was 3.5 (SD = 1.0) years. This result may show that the damage caused by nonnutritive sucking habits can be corrected spontaneously after cessation of these habits.…”
Section: Discussioncontrasting
confidence: 53%
“…20 Age was the only variable associated with malocclusion, in agreement with findings reported in the literature. 3,4,9,25 The greater prevalence of malocclusion at younger ages suggests self-correction over time. 3,4 However, these findings should be viewed with some latitude, seeing that any type of occlusal abnormality was considered malocclusion; this could also be considered a limitation to the present study.…”
Section: Resultsmentioning
confidence: 99%
“…6,25 Whereas a number of authors argue that children with greater purchasing power and those whose mothers have a lower schooling level are more likely to develop malocclusion due to greater access to and frequency of pacifier use, 29,30 no significant associations were found in the present study between socioeconomic indicators and malocclusion, in agreement with findings reported in previous studies. 6,9 It seems that another factor unassociated to social class has occurred, namely the greater participation of women in the workforce, with a consequent reduction in breastfeeding and greater susceptibility to the adoption of nonnutritive sucking habits. 7,25 Moreover, genetic and environmental factors can affect children 6 regardless of social class.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is expected that, at 3 years of age, the child is able to give up sucking habits 15 , thus reducing the risk of malocclusion 19 .…”
Section: Discussionmentioning
confidence: 99%